Desafios e experiências na UNATI de Botucatu - Oliveira, Letícia Patrocínio [UNESP] (2015)
The Universidade Aberta à Terceira Idade (UNATI) is a project that promotes the social integration of the elderly with activities of different ways, trying to motivate them, encourage them and teaching them.